The Effect of Accounting Information Systems (AIS), Leadership Style, Motivation, and Working the environment on the Employee’s Performance at Badan Keuangan Daerah (BKUD) Regency Semarang - Dyah Pramesti Nur Azizah; Mohamad Hasanudin; Toni Hartono (Yayasan Ilomata, 2020)
This study aims to determine whether the Accounting Information System, Leadership Style, Motivation, and Work Environment together have a significant effect on the Performance of Employees at Badan Keuangan Daerah (BKUD) Kabupaten Semarang. Samples that met the criteria in this study were 65. The analysis used is multiple regression analysis preceded by a classic assumption test consisting of the normality test, multicollinearity test, and heteroscasticity test. While hypothesis testing is done using the F test and t test. The results of data analysis or regression results indicate that partially the Accounting Information System, Leadership Style, Motivation, and Work Environment influence employee performance. Simultaneously the Accounting Information System, Leadership Style, Motivation, and Work Environment contributed 84.6% of the effect on the level of the dependent variable, namely employee performance.